1952
DOI: 10.1017/s0080455x00009942
|View full text |Cite
|
Sign up to set email alerts
|

XX.—The Rate of Growth ofVenerupis pullastra(Montagu) at Millport, Scotland

Abstract: SynopsisMarking experiments have demonstrated that certain of the rings appearing as surface sculpture on the shells of the lamellibranch Venerupis pullastra are valid as a measure of annual growth. From measurement of these rings the mean monthly and the mean annual growth increments have been calculated. The length-age relationship curve is similar to that of most other lamellibranchs. Reasons for the variation in the mean monthly rate of growth have been examined. The height-length and the thickness-length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1961
1961
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In 1953 and 1955 some of the Thais were numbered with India ink on a small part of the shell which had been filed clean. When dry, the number was covered with a mixture of "Distrene," a transparent plastic, dissolved in xylol, as described by Quayle (1952).…”
Section: Population Density Of Thaismentioning
confidence: 99%
“…In 1953 and 1955 some of the Thais were numbered with India ink on a small part of the shell which had been filed clean. When dry, the number was covered with a mixture of "Distrene," a transparent plastic, dissolved in xylol, as described by Quayle (1952).…”
Section: Population Density Of Thaismentioning
confidence: 99%
“…Adult P. margaritifera showed reduced or no increase in height during July, August and September, coinciding with its spawning season. Many investigators found similar relations between a reduced growth rate and spawning in other bivalves (Weymouth, 1923;Quale, 1952;Orton, 1928). After the spawning season, the height-increase rose to decrease again in December and January.…”
Section: Discussionmentioning
confidence: 69%